Pengaruh Harga Minyak Dunia, Suku Bunga, Inflasi, IHSG, Dan Neraca Perdagangan Terhadap Nilai Tukar - Dita Nurul Aini Mustika Dewi; Lily Sri Utami; Rohmah Dini Ayunda Mustofa (LPMP Imperium, 2021)
This study aims to determine the effect of fluctuations in world oil prices, the BI 7 Days Reverse Repo Rate reference rate, inflation, JCI and also the trade balance on the exchange rate both in the long term and in the short term. One of the economic indicators that is sensitive and vulnerable to global fluctuations and has the potential to become a systematic risk is exchange rate movements. Management of exchange rate stabilization is necessary to strengthen the domestic economy. Several studies have shown that there is a relationship and correlation between world oil, benchmark interest rates, inflation and the trade balance on the exchange rate. The method used in this study is the Vector Error Correction Model (VECM) in order to determine the long-term and short-term movements. Coupled with the analysis of the Impulse Response Function (IRF) which can determine the fluctuations of each variable and Variance Decomposition which can determine the source of the fluctuations. The variables used in this study include world oil prices, BI 7-days repo rate, inflation, trade balance, JCI and the exchange rate of the rupiah against the US dollar. The results of this study indicate that world oil prices have a significant effect on the exchange rate in the long run. In the short term, the JCI last period had a significant effect on the exchange rate. The fluctuations in the exchange rate, BI 7-day repo rate, JCI, inflation, trade balance, and also world oil prices will affect the movement of exchange rates in Indonesia. At the beginning of the turbulence period, the JCI also came from the JCI, but over time it could be controlled.